Occurrence of Rhodococcus equi in soil and faeces in selected study farms in Malaysia - M., Fithri; Zakaria, Zunita; Hassan, Latiffah; Mohamed Mustapha, Noordin (Department of Veterinary Services Malaysia, 2012)
The world widely distributed infection by Rhodococcus equi usually leads to pneumonia and associated respiratory signs. This study is aimed at detecting the occurrence of this pathogen in selected horse farms. A total of 12 R. equi isolates from few samples (13.89%)were successfully obtained from soil and faeces collected from two selected farms. However, based on the vapA gene classification, only one virulent R. equi isolate was identified.